Biochemical composition and nutritional value of green mass of the sainfoin varieties and promising lines - N. S. Kravchenko; S. A. Ignatiev; N. G. Ignatieva; A. A. Regidin (Зерновое хозяйство России, 2023)
There have been presented the study results of the biochemical composition of the green mass of sandy sainfoin (Onobrychis arenaria) samples developed by the FSBSI Agricultural Research Center “Donskoy”. The purpose of the current study was to identify the variability of the content of raw nutrients: protein, oil, fiber, ash, BEV in the green mass of sainfoin varieties and lines, to determine the amino acid composition of protein and to identify the best samples for the studied traits. The study was carried out in the period of 2017–2021. The variety ‘Zernogradsky 2’ was used as a standard variety. Biochemical analyzes were carried out in the period ‘budding stage – blooming stage’. The chemical composition of the selected samples was carried out in accordance with the methodology and GOSTs. The maximum crude protein percentage was determined in promising lines ‘Sin 8/95’ (15.38 %) and ‘Sin 13/95’ (14.72 %). There was found that the varieties ‘Veles’ (10.6 %), ‘Atamansky’ (14.1 %) and the lines ‘Sin 13/95’ (11.8 %), ‘Sin 8/95’ (16.9 %) were characterized by a high concentration of raw ash. The optimal fiber content was established in the varieties ‘Atamansky’ (29.73 %) and ‘Veles’ (29.61%). As a result of determining the amino acid composition of protein, there was found that the line ‘Sin 8/95’ (68.5 g/kg) and the varieties ‘Zernogradsky 2’ (62.3 g/kg), ‘Veles’ (52.5 g/kg) were distinguished by the collection of essential amino acids. The varieties ‘Veles’ (75.0 g/kg), ‘Zernogradsky 2’ (66.5 g/kg) and the line ‘Sin 8/95’ (66.4 g/kg) were distinguished by the number of non-essential amino acids. The line ‘Sin 8/95’ (134.9 g/kg) and the varieties ‘Veles’ (127.5 g/kg), ‘Zernogradsky 2’ (128.8 g/kg) were characterized by a high total collection of amino acids. There was determined that crude protein percentage (from 4.3–18.4 %), fiber (7.8–16.9 %), dry matter (4.5–13.1 %) and BEV (9.6–15.9 %) were characterized by slight and medium variation in values. The content of crude ash (9.6–25.2 %) and crude oil (7.5–27.8 %) had weak, medium and strong variations depending on the variety and line. The study of the biochemical composition of sainfoin made it possible to establish varietal differences and variability of traits that characterize the nutritional value of the feed. The varieties ‘Veles’, ‘Zernogradsky 2’ and the promising line ‘Sin 8/95’ were found to have the best quality traits, which could be recommended for use in the breeding process as sources of useful traits and properties.